A Retrospective Clinical Study on Factors Influencing the Failure of NCCL Restorations - Wanchanok Saengnil; Munlika Anuntasainont; Natchalee Srimaneekarn; Vesna Miletic; Pong Pongprueksa (Hindawi Limited, 2022)
Objectives. This retrospective study evaluated the factors influencing the clinical failure of noncarious cervical lesion (NCCL) restorations. Methods. Patients were routinely treated by undergraduate or postgraduate students and randomly received a clinical recall evaluation. A retrospective study was performed with two experienced calibrated examiners to evaluate NCCL restorations, including the critical parameters of retention, caries, marginal discoloration, and marginal integrity. The factors related to the restoration included gender, age, arch site, tooth position, the presence of occlusal wear facets, caries risk, operator, adhesive strategy, and composite. The clinical failure comparison between the parameters and factors was performed using the binary logistic regression analysis. Results. A total of 460 cervical restorations from 96 patients were evaluated. The adhesive strategy and the presence of occlusal wear facets were the most important factors influencing the parameter failure. Therefore, the highest failure was marginal integrity, in which the gingival marginal integrity failure was 50.7%, and the occlusal marginal integrity failure was 42.4%. Conclusions. The main factors influencing clinical failure for partial loss, marginal discoloration, and marginal integrity were the adhesive strategy and the presence of occlusal wear facets. Therefore, marginal integrity was the most frequent failure parameter.